Understanding Perspectivism Scientific Challenges and Methodological Prospects - Massimi, Michela; McCoy, Casey D. (Routledge Studies in the Philosophy of Science, 2020)
This edited collection is the first of its kind to explore the view called perspectivism in the philosophy of science. The book brings together an array of essays that reflect on the methodological promises and scientific challenges of perspectivism in a variety of fields such as physics, biology, cognitive neuroscience, and cancer research, just for a few examples. What are the advantages of using a plurality of perspectives in a given scientific field and for interdisciplinary research? Can different perspectives be integrated? What is the relation between perspectivism, pluralism, and pragmatism? These ten new essays by top scholars in the field offer a kaleidoscopic journey toward understanding the view called "perspectivism" and its relevance to science.